ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN TAKSI BLUE BIRD SURVEI DI POOL RADIN INTEN JAKARTA TIMUR - Rully Arifiansyah (LPPM Universitas Asa Indonesia, 2018)
Customers’ satisfaction is one of the key of success of a company in maintaining its existence in the market, especially with increasing competition and various companies’ strategies in offering products and services. This study aimed to determine consumers’ assessment on services provided to customer satisfaction and loyalty. This study was performed with survey method which involved 116 respondents who were the customers of PT. BlueBird Group Radin Inten pool taxi. From the survey, data was processed using SEM method with the help of LISREL 8.80 program. Research results proved that service quality had positive and significant influence on customers’ satisfaction. Also the influence of customers’ satisfaction on customers’ loyalty was proven. However these results don’t support the hypothesis that there is an influence of service quality on customers’ loyalty. Based on the results of the analysis, the dimensions of service quality which must be maintained are responsiveness, assurance and empathy because they can explain service quality.